Arc flash hazard analysis of coal-fired power station - Gould, J.; Wolfs, Peter (2016)
© 2016 IEEE. Arc flash presents a considerable safety and operational hazard to any site with electrical reticulation. Managing the hazard is key to ensuring the safety of workers and minimizing the downtime of plant and equipment. Different standards available for quantifying the hazard are examined and applied to measure the hazard at a coal-fired power plant in the Central Queensland region. The case study is supplied by Stanwell Power Station. The final section discusses the outcome of performing arc flash analyses, the benefits of such a study and key conclusions relevant to industry.